Adult Education and context information society - Joaquín GARCÍA CARRASCO (Ediciones Universidad de Salamanca, 2009)
Adult education and sociocultural context are interdependent concepts. The news consists of the any adult person is considered today a genuine subject of formation. How should the educational system respond to these facts? The cultural contingency of the XXI century modifies the framework for the conception of the basic education, the emotional differentials of the cultural issues, the environments of formation and the necessary reconstruction of formative resources. All of it modifies the requirements of the professional formation.